Si1–xGex nanocrystals as sensitive elements for magnetic field and temperature sensors - DruzhininА. A.; OstrovskiiІ. P.; KhoverkoYu. М.; NichkaloS. І.; KoretskiiR. М. (Technology and design in electronic equipment, 2012)
The paper deals with investigation of magnetic field effect on electrophysical properties of Si1–xGex nanowhiskers at low temperatures. It was shown that field dependence of resistance of Si1–xGex nanowhiskers samples doped to concentrations near the dielectric side of metal-insulator junction possesses the linear character. The concept of making sensors on the basis of Si1–xGex nanowhiskers detecting simultaneously magnetic field and temperature has been proposed.